2002
DOI: 10.1103/physrevlett.88.095003
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically Induced Transparency in Ensembles of Classical Oscillators

Abstract: We develop a classical model of the parametric effect of electromagnetically induced transparency (EIT) within the line of resonance absorption of an electromagnetic wave in the medium--an effect initially discovered for a quantum three-level system. On the basis of this model, the EIT effect for electromagnetic waves at frequencies of the electron-cyclotron resonance in a cold plasma is considered. Similar to the analogous quantum scheme, the EIT window in the classical model is characterized by group deceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 15 publications
4
69
0
Order By: Relevance
“…Recently it was theoretically found that a magnetized plasma can be made transparent to a right-hand polarized wave (probe) at the cyclotron frequency in the presence of strong pump wave which is detuned by the plasma frequency [1][2][3]. This is a classical analogy of the quantum electromagnetically induced transparency (EIT) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was theoretically found that a magnetized plasma can be made transparent to a right-hand polarized wave (probe) at the cyclotron frequency in the presence of strong pump wave which is detuned by the plasma frequency [1][2][3]. This is a classical analogy of the quantum electromagnetically induced transparency (EIT) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…An electromagnetically induced transparency (EIT) [1], the well-known quantum phenomenon in contemporary nonlinear optics, has a classical counterpart in plasma physics, an effect of the magnetized plasma transparency at the cyclotron frequency [2,3]. This phenomenon is caused by an appearance of a transparency band within the resonance absorption zone in the presence of either a strong electromagnetic wave or a magnetostatic undulator, allowing propagation of electromagnetic waves in the normally opaque medium.…”
Section: Introductionmentioning
confidence: 99%
“…There are many interesting phenomena in quantum optics and atomic physics, induced by quantum coherence and quantum interference. Examples include electromagnetically induced transparency (EIT) [1,2,3]], coherent population trapping (CPT) [4], cancelation of spontaneous emission [5], superluminal and subluminal light propagation [6,7], lasing without inversion [8,9], and so on. The effect of electromagnetically induced transparency (EIT) has led to many interesting nonlinear optical phenomena.…”
Section: Introductionmentioning
confidence: 99%